2020
DOI: 10.3390/metabo10060245
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Volatile Organic Compounds during Inflammation Induced by TNF-α in Ventilated Rats

Abstract: Systemic inflammation alters the composition of exhaled breath, possibly helping clinicians diagnose conditions such as sepsis. We therefore evaluated changes in exhaled breath of rats given tumor necrosis factor-alpha (TNF-α). Thirty male Sprague-Dawley rats were randomly assigned to three groups (n = 10 each) with intravenous injections of normal saline (control), 200 µg·kg−1 bodyweight TNF-α (TNF-α-200), or 600 µg·kg−1 bodyweight TNF-α (TNF-α-600), and were observed for 24 h or until death. Animals were ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Another window to the possibility that microbial genes, pathways, and metabolites are interacting within the host to alter its immune response is the use of exhaled lung air, what some have termed a "gas lavage." [48][49][50] Use of multiple analytic technologies including multicapillary column-ion mobility spectrometry, thermal desorption-gas chromatography mass spectrometry, and others have been employed to detect both volatile and nonvolatile organic compounds that reflect both host tissue metabolism and microbial metabolism. [48][49][50] For example, indoles, metabolites produced exclusively by commensal and pathogenic microbes within the gut and lung, are known to bind to the aryl hydrocarbon receptor and activate macrophages, key immune cells that clear infection.…”
Section: Exhaled Air -Another Compartment For Microbial Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Another window to the possibility that microbial genes, pathways, and metabolites are interacting within the host to alter its immune response is the use of exhaled lung air, what some have termed a "gas lavage." [48][49][50] Use of multiple analytic technologies including multicapillary column-ion mobility spectrometry, thermal desorption-gas chromatography mass spectrometry, and others have been employed to detect both volatile and nonvolatile organic compounds that reflect both host tissue metabolism and microbial metabolism. [48][49][50] For example, indoles, metabolites produced exclusively by commensal and pathogenic microbes within the gut and lung, are known to bind to the aryl hydrocarbon receptor and activate macrophages, key immune cells that clear infection.…”
Section: Exhaled Air -Another Compartment For Microbial Analysismentioning
confidence: 99%
“…[48][49][50] Use of multiple analytic technologies including multicapillary column-ion mobility spectrometry, thermal desorption-gas chromatography mass spectrometry, and others have been employed to detect both volatile and nonvolatile organic compounds that reflect both host tissue metabolism and microbial metabolism. [48][49][50] For example, indoles, metabolites produced exclusively by commensal and pathogenic microbes within the gut and lung, are known to bind to the aryl hydrocarbon receptor and activate macrophages, key immune cells that clear infection. 51 Indoles can be directly detected in lung gas, expelled stool, and plasma.…”
Section: Exhaled Air -Another Compartment For Microbial Analysismentioning
confidence: 99%
“…Previous literature has shown that particulate matter has adverse health effects on the respiratory and cardiovascular system, in which fine and ultrafine particles (UFP) can induce pulmonary as well as systemic inflammation [ 5 , 6 , 7 , 8 ] and oxidative stress [ 9 , 10 ]. Such processes have been shown to be reflected in exhaled breath patterns of ventilated rats and patients with asthma or chronic obstructive pulmonary disease (COPD) [ 11 , 12 , 13 ]. Therefore, we hypothesize that exposure to air pollution could be detected in the exhaled breath profile.…”
Section: Introductionmentioning
confidence: 99%